THE EFFECT OF ENTREPRENEURIAL ORIENTATION ON ENTREPRENEURIAL INTENTION: SELF- EFFICACY AS A MEDIATIOR (Case Study on Young Entrepreneurs in Surabaya) - Christina Yanita Setyawati; Geraldo Ricky (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Indonesia is one of the countries that are focusing on encouraging its people to become an entrepreneur. This research was conducted to know the causes of many failed student businesses with the aims to determine the effect of entrepreneurial orientation on the entrepreneurian intention with self-efficacy as a mediating variable on young entrepreneurs in Surabaya. The data was collected by distributing questionnaires directly to the respondents using the Likert scale 1-5. The population of this study is 474 young entrepreneurs who are students of Ciputra University in Surabaya who are currently in business. The sampling method used was convenience sampling with sampling techinique using Hair et al., calculation producing 102 respondents. The data were analyzed using validity test, reliability test, classic assumption test, hierarchial regression test, and hypothesis test. The results of this study showed that (1) entrepreneurial orientation has a significant effect on self-efficacy; (2) self-efficacy has a significant effect on entrepreneurship intentions; (3) entrepreneurial orientation have a significant effect on entrepreneurial intentions; (4) and entrepreneurial orientation have a significant effect on entrepreneurial intentions after being mediated with self efficacy. Keywords: Entrepreneurial Intentions, Entrepreneurial Orientation, Self Efficacy